PENERAPAN PIDANA TERHADAP PELAKU DAN RESTITUSI TERHADAP ANAK SELAKU KORBAN TINDAK PIDANA KEKERASAN SEKSUAL - Toga, Amos Chandra; Radisman Saragih; Lonna Yohanes Lengkong (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The criminal act of sexual violence against children is increasing, this can be done by anyone, even by their own family. as a state of law Indonesia has a set of rules for punishing the perpetrator, one of which is imprisonment, but imprisonment is not enough to give a sense of justice to the victim, because in this case the victim suffers a lot. therefore the victim must provide compensation for the suffering suffered by the victim, called restitution. The research method used in this paper is a juridical-normative legal research method with a law approach and a case approach. The data used are secondary data consisting of primary, secondary, and tertiary legal materials. The results of this research on the Wonosobo District Court Decision Number 26/Pid.Sus/2020/Pn Wsb about the imprisonment of the defendant it has given a sense of justice and the implementation of the victim’s right of restitution. The defendant is sentenced to 10 years in prison and has an obligation to pay the right of restitution to the victim in the amount of Rp. 6,364,000.00 (six million three hundred sixty four thousand rupiah).